Customer Perception of Online Claim Service Applications on Car Insurance - Anggia N. Sasanti; Cahyadi P Putra; Harry Soesanto (Jurnal Manajemen Bisnis, 2022)
The decrease in premium income and the increase in the number of claims will erode the profits of insurance companies so that one of the strategies carried out by insurance companies during this pandemic is to encourage the use of online claim service technology to minimize costs in the claims management process. In this study, the authors took the subject of customer interest in online claim service technology in four-wheeled vehicle insurance and the level of adaptation or acceptance of customers to the claim service technology offered by insurance companies. The author uses the TAM (Technology Acceptance Model) model to develop and test variables for perceived of use and perceived of usefulness variables that affect customer interest in using online claim service applications (Davis, 1989). In addition, the author also develops and conducts tests for variable perceptions of customer trust in company competencies to find out whether the company's competence can affect customer attitudes and interests in using claim service applications.